Culm anatomy of the genus Otatea (Poaceae, Bambusoideae, Bambuseae, Guaduinae) as a contribution to Mexican species identification - García-Martínez, Miguel A.; Terrazas, Teresa; Sánchez, Daniel; Carrillo-Reyes, Pablo; Ruiz-Sanchez, Eduardo (Phytotaxa, 2023)
Otatea is a Neotropical woody bamboo genus with thirteen described species. It is distributed from Mexico to Central America and northeastern Colombia. In Mexico, the archaeological evidence suggests that the culms of Otatea have been used for centuries by some ethnic groups. It is important to explore morphological and anatomical characters for species identification in woody bamboos as consequence of its monocarpic nature. Most studies on culm anatomy are centered on commercially used species describing their physical and mechanical properties. The aim of this work was to find culm anatomical characters with taxonomic value. To perform this, we collected internode samples from adult plants at mid culm of 15 specimens that represent 10 described species and two putative new species of Otatea. Our results include descriptions of culm anatomy at a cross section accompanied with images that detail all the structures measured and described. Additionally, we elaborate a key based on anatomical characters. This contribution is the first to explore culm anatomy of the genus Otatea in search for characters with taxonomic value, providing useful evidence for species identification, including samples from archaeological sites.